Kajian Tafsir Rawa’iul Bayan terhadap Al-Qurtubi tentang Batasan Mengusap Kepala saat Wudhu: Analisis Intertekstual Julia Kristeva - Nadlif, Ahmad (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
The verse about wudu in QS. al-Maidah: 6, which reads "wamsahu bi ru’usikum," has a dzanni ad-dalalah meaning, which leads to differences in interpretation among scholars. This study aims to analyze the differences in the interpretation of the verse on the limits of wiping the head during wudu between the tafsir Rawai’ul Bayan and al-Qurtubi. Using a semantic and intertextual approach based on Julia Kristeva’s theory, this research explores the significance and signifiance of the verse as well as the intertextual relationships between the two tafsirs. By employing a qualitative method, this study analyzes the texts of both tafsirs and finds that Rawai’ul Bayan tends to interpret "wiping the head" minimally, suggesting wiping only part of the head. On the other hand, al-Qurtubi offers a broader interpretation, allowing the wiping of the entire head or at least a quarter of it. The intertextual analysis reveals relationships of modification and conversion between the two tafsirs, indicating a reciprocal influence in the interpretation process. This study concludes that the differences in interpretation are influenced by factors such as social, cultural, and methodological contexts in the tafsir approaches used by each mufassir. The contribution of this research is to enrich the understanding of the dynamics of interpreting the wudu verse from both classical tafsir perspectives and intertextuality, offering new insights for contemporary tafsir studies.